Paradigma Model Legislasi dan Tujuan Penguatan Sistem Presidensial Republik Indonesia - Hartama, Aldi Yoga (Jurnal Hukum & Pembangunan, 2023)
One of the five basic agreements in the constitutional amendment is to strengthen the presidential system. However, the legislative practices that have been running so far tend to move away from the character of legislation in the presidential system itself. This paper tries to suggest the dynamics of the legislative model that runs after the 2002 constitutional amendment. At the same time, it will discuss how the legislative process should be carried out in a presidential system of government and its comparison with the legislative process in a parliamentary system of government.